Renewable energy, GDP and CO2 emissions in high-globalized countries - Mirziyoyeva, Ziroat; Salahodjaev, Raufhon (Frontiers in Energy Research, 2023)
Introduction: Policymakers devote significant efforts to decrease CO2 emissions, as climate change has Q7 numerous adverse impacts on society. While the global level of CO2 emissions has been gradually rising since the 1990s, the highest growth was observed in low- and middle-income economies. This study differs from nascent research as it fills the gap by exploring the GDP-energy-CO2 emissions nexus for the top 50 highly globalized countries under analysis. Our study explores the multidimensional relationship between economic growth, renewable energy, globalization, and climate change, using CO2 emissions as a proxy for air pollution, and focusing on the most globalized countries. Methods: In this study, we rely on dynamic panel estimators such as the two-step system GMM estimator. System GMM estimator is recommended to use with the panel data when 1) the correlation between a dependent variable and its lag is above 0.8; and 2) the number of countries (i.e., 50 countries) exceeds the time frame (i.e., 19 years). As our study design fits these conditions, we use extension of a two-step system GMM estimator which restricts the expansion of instruments. Moreover, a two-step system GMM estimator is especially efficient as it controls for heteroskedasticity. Results: We find that renewable energy and globalization decrease CO2 emissions. If causal, a 1 percentage point increase in the share of renewable energy in total energy consumption leads to a 0.26% decrease in per capita CO2 emissions. Similarly, we find that a larger representation of women in national parliament contributes to the reduction in CO2 emissions. GDP per capita has an inverted U-shaped relationship with CO2 emissions and the turning point is approximately 67,200 international dollars adjusted for PPP. Discussion: Our results suggest that renewable energy significantly contributes to the reduction of carbon emissions while GDP per capita has an inverted U-shaped link with CO2 emissions. Thus, we confirm the presence of the EKC hypothesis for highly-globalized countries. Consequently, our study offers several policy implications. Firstly, it is important for developing countries to increase the share of energy consumed from renewable energy sources. This will have a positive effect not only on air quality, but also on economic growth. Thus, it is essential to increase investment in the renewable energy sector and create conditions and benefits for the rapid adoption of renewable technologies by the private sector and households. Secondly, it is crucial to increase the quality of investment climate. Developing countries can significantly gain from globalization-driven FDI as this can lead to technology transfer, especially in the energy sector. Thirdly, our results suggest that improving female empowerment can significantly reduce the vulnerability to climate change. This can be achieved by increasing women’s human capital and investing in women-led organizations and communities.